Application of Blue Ocean Strategy (BOS) towards effective leaders in public sector - Zakaria, Zaki; Silong, Abu Daud; Ismail, Mohd Bakhari (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Blue Ocean Strategy (BOS) is an analytical tool for business strategy to remain competitive based on three principles namely high impact, low cost and fast execution. In making BOS produces desired result, these three principles are well supported by two core values in the form of creativity and innovation. In fact, BOS has been increasingly become popular after its introduction in 2005 by Prof Chan Kim and Prof Renee Mauborgne. Meaning to say, BOS is a new concept for business industry to remain relevant by delivering high value of products while lowering the cost. It encourages business leaders to think out of the box by creating a new Blue Ocean for their business to thrive. It also provides systematic approach and effective analytical framework for companies to swim in the new creation of Blue Ocean instead of competing in bloody ‘Red Ocean’. The idea is to make competition irrelevant as companies are expected to perform well in their own Blue Ocean. The result is tremendously great as companies are able to come up with ‘value innovation’ that create powerful leap to the firms besides unleashing new demand. The idea of creating new ‘Blue Ocean’ of opportunities has attracted the attention of government of Malaysia to apply BOS principles in public service in 2009. In that year, Malaysia has new Prime Minister and he is much attached to the three principles in BOS. These three principles are driven by creativity and innovation which has been identified as a nucleus for nation development. As Malaysia is pursuing towards an advanced nation by 2020, Prime Minister realized government need a quantum leap as the conventional way of implementing government programs were not effective anymore. The current stigma of looking for increased budget to implement government initiatives must be halted among public sector leaders. They need to be transformed towards becoming effective leaders as this will contribute for greater productivity and better performance. The good aspect of BOS is not just focus on strategies but more importantly about people. It injects creativity and innovation in leaders thinking that make the way for greater collaboration across government agencies. The issues of limited budget, time constraint and manpower resources can be overcome once public sector leaders embrace BOS principles. In fact, BOS has result in a quiet internal revolution on how government of Malaysia do ‘businesses’ for the benefit of people on the ground. As such, BOS has been placed as the main driving force in the current 11th Malaysian Plan (2016 – 2020) with the theme ‘anchoring growth on people’. Since undertaking BOS, more than 90 government project initiatives have taken place that recorded resounding success which are high impact, fast executed and at lower cost. This concept paper will highlight how BOS has successfully transform leaders in public sector to reinvent themselves by becoming more innovative, creative, motivated, portray strong teamwork and breaking down silo mentality. It also demonstrate how leaders in public service collaborate and work together by applying BOS concept in gunning for the same goal that is to make Malaysia a fully developed nation in 2020.